Commercial law in a nutshell - MacIntyre, Ewan (Nutshells, 2006)
Presenting the essentials of commercial law, this work explains the basic principles, and analyses cases. It includes cases on the meaning of 'acceptance'; sets out the additional rights of buyers in consumer cases; and considers the rights and duties of self-employed commercial agents. It also contains an examination checklist.